2011
DOI: 10.1115/1.4002845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combustion Chamber Geometry Deviations Upon Exit Temperature Profiles for Populations With Varied Service Limitations

Abstract: The purpose of this continuing research was to investigate the effects of combustion chamber geometry on exit temperature fields using a validated ambient pressure test rig. Rig test conditions were set to simulate an engine operating condition of 463 km/h (250 kn) at 7620 m (25,000 fl) by matching Mach number, equivalence ratio, and Sauter mean diameter of the fuel spray. Using a thermocouple rake, high resolution temperature measurements were obtained in the combustion chamber exit plane. Following the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…For strong flow penetration, the size of the passage holes was increased by 1.15 times the size of the largest passage hole in the secondary zone in order to achieve better flow penetration effect without damaging the combustor liner walls. 8 The number of the passage holes per row was kept similar to that in the secondary zone and was evenly distributed circumferentially across the combustor geometry. The schematic diagram of the passage holes situated at the combustor outer liner is shown in Figure 11.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For strong flow penetration, the size of the passage holes was increased by 1.15 times the size of the largest passage hole in the secondary zone in order to achieve better flow penetration effect without damaging the combustor liner walls. 8 The number of the passage holes per row was kept similar to that in the secondary zone and was evenly distributed circumferentially across the combustor geometry. The schematic diagram of the passage holes situated at the combustor outer liner is shown in Figure 11.…”
Section: Results and Analysismentioning
confidence: 99%
“…Kotzer et al. 8 investigated the effects of the combustor chamber geometry on the exit temperature profiles. The results showed that small deviations in the combustor geometry could influence the temperature profile significantly, reflecting the strong sensitivity of internal flow pattern on the temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that relatively small deviations in the spray pattern from a nominal distribution can translate into dramatic changes in the exit temperature distributions. Clayton et al 6 experimentally investigated the effect of combustion chamber geometry in the dilution zone on the exit temperature fields by using thermocouple rakes. They demonstrated that the pattern factor increases with the increase in the dilution zone geometry distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various combustor design parameters such as fuel nozzle spray patterns, dilution hole geometry, fuel type, swirl number and different fuel injection methods on combustor exit pattern factor has been reported by authors. [5][6][7][8][9] The effect of combustor swirling flow (swirl number) on recirculation zone, flame speed, flame area, primary jet flow and flare geometry was reported by previous studies. [10][11][12][13] The effect of combustor inlet swirl angle (compressor discharge) on pattern factor and pressure loss still remains a gap which is addressed in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation